The effects of enteral supplementation of glutamine and arginine in lipopolysaccharide (LPS) induced sepsis - Okan Bakır, Binnur; Öztezcan, Serdar; Saka, Mendane; Karaltı, İskender; Özkan, Ferda; Akçil Ok, Mehtap (Progress in Nutrition, 2019)
Sepsis is the leading cause for death in critically ill patients. While the exact mechanisms are not clear, multiple organ dysfunction syndrome induced by sepsis might cause mitochondrial dysfunction. Spesific nutrients may help regulating immunological and inflammatory responses. Glutamine and arginine amino acids have both important roles in growth, tissue repair, cell renewal and collagen synthesis. There are different results of studies with immunmodulatory nutrients in critically ill patients such, they have no effect on mortality or decrease sepsis incidance. The aim of this study is to evaluate the effects of enteral supplementation of glutamine, arginine and glutamine and arginine combination in lipopolysaccharide (LPS) induced sepsis. Twenty eight male Sprague Dawley rats were randomly divided into four groups: Glutamine, Arginine, Glutamine + Arginine and Control. Glutamine group received 500 mg/kg/day glutamine, Arginine group recieved 500 mg/kg/day arginine, Glutamine + Arginine group received 250 mg/kg/day glutamine and 250 mg/kg/day arginine containing suspension. Rats were fed for 10 days and 3 mg/kg LPS was implemented. 24 hours later, all rats were sacrified. C-Reactive Protein (CRP), Interleukin (IL)-1β, IL-6, Tumor Necrosis Factor-α(TNF-α), Aspartat aminotransferase (AST) and Alanine aminotransferase(ALT) levels were studied, livers were examined histopathologically. Serum TNF-α levels were significantly lower in Glutamine + Arginine group in comparison with Control group. Liver histopathology analysis showed that apsis, hepatocyte damage, kupffer cell proliferation and portal inflammation were more frequent and severe in control group than all groups. These results revealed that enteral supply of glutamine, arginine and their combination have positive effects on liver damage and inflammation.